DETERMINASI INDEKS PEMBANGUNAN MANUSIA DI PROVINSI ACEH: KAJIAN EMPIRIS DATA PANEL KABUPATEN/KOTA - Ramadhani, Putri; Noviar, Helmi; Ariani, Dian; Badli, Saiful; Ertika, Yenny (Universitas Teuku Umar, 2025)
This research is intended to analyze the effects of Gross Regional Domestic Product (GRDP), Local Own-Source Revenue (LOSR), Capital Expenditure (CapEx), and the Aceh Special Autonomy Fund (ASAF) on the Human Development Index (HDI) in Aceh Province over the period from 2019 to 2023. The study employs a panel data regression approach utilizing the EViews 10 software to evaluate the proposed hypotheses. The variables incorporated in this analysis include GRDP, PAD, BM, DOKA, and HDI. The data utilized consists of secondary data, combining time series and cross-sectional datasets spanning 2019 to 2023. The estimation findings reveal that individually, Gross Regional Domestic Product (GRDP) exerts a significant and favorable impact on the Human Development Index (HDI) within Aceh Province, supported by statistical significance; PAD demonstrates a positive yet statistically insignificant effect on HDI; BM also shows a positive but non-significant impact; In contrast, the Aceh Special Autonomy Fund (DOKA) demonstrates an inverse and statistically meaningful connection with The Human Development Index (HDI). When combined, these variables jointly exert a positive and statistically significant effect on the Human Development Index (HDI) throughout Aceh Province.